Non-contiguous finished genome sequence of Staphylococcus capitis CR01 (pulsetype NRCS-A). Issue 3 (November 2014) - Lemriss, H.; Simões, P.; Lemriss, S.; Butin, M.; Ibrahimi, A.; Kabbaj, S.; Rasigade, J.; Laurent, F.
Abstract Staphylococcus capitis is a coagulase-negative staphylococcus (CoNS) commonly found in the human microflora. Recently, a clonal population ofStaphylococcus capitis (denominated NRCS-A) was found to be a major cause of late-onset sepsis (LOS) in several neonatal intensive care units in France. Here, we report the complete genome sequence and annotation of the prototypeStaphylococcus capitis NCRS-A strain CR01. The 2, 504, 472 bp long genome (1 chromosome and no plasmids) exhibits a G+C content of 32.81%, and contains 2, 468 protein-coding and 59 tRNA genes and 4 rRNA genes.